Optimizing Lime Mordant Conditions for Cotton Dyeing with Dragon Fruit Peel Extract - Syamsuddin Syamsuddin; Jusman Jusman; Indriani Indriani; Ni Ketut Sumarni; Yulina Christien Morokuhi (Postgraduate, University of Mataram, 2026)
This study investigates the extraction and application of natural colorants from dragon fruit (Hylocereus polyrhizus) peels for cotton fabric dyeing. A maceration process produced a concentrated anthocyanin-rich extract, with absorption peaks at 475 nm and 536 nm. Experiments were conducted using a completely randomized design with three replicates per treatment. The effects of lime (Citrus aurantifolia) mordant concentration, pH, and immersion time on dye uptake and retention were measured using UV-Vis spectrophotometry. Dye retention, calculated from absorbance differences before and after fabric immersion and post-wash, served as an indicator of color stability. Optimal retention was observed at 2% mordant concentration and pH 6.5, with absorbance-based dye retention values of 0.212 at 475 nm and 0.215 at 536 nm. Higher mordant concentrations and lower pH reduced dye stability and brightness, while immersion time significantly influenced retention, with peak values at 475 nm after 30 minutes and improved retention at 536 nm after 120 minutes. These results demonstrate the potential of dragon fruit peel extract as an eco-friendly textile dye and highlight the importance of optimizing mordant concentration, pH, and immersion time to achieve vibrant, durable colors.